PEMBERDAYAAN MASYARAKAT DALAM PENGOLAHAN MINUMAN KESEHATAN INSTAN SEBAGAI PENINGKATAN DAYA TAHAN TUBUH DI RT 04/RW01 DESA MENDALO INDAH - Riski Gusti, Diah; Marlinda, Lenny; Ekasari, Munifilia; Erliana, Dina; Rahmi, Rahmi; Pratiwi, Nurul; Nuraini, Syafira; Putri Pandulu, Clara; Yusria Putri, Desta; Fitri, Selta; Wahyuningsih, Iga (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2026)
Mendalo Indah Village has great potential for trade because of its strategic location near two major universities in Jambi Province, namely Jambi University and UIN Sultan Thaha Jambi. Students in this area have a strong preference for instant food and beverages as a result of their busy academic and practicum schedules. The urgency of this community service activity lies in the need for instant but natural health supplements among students, as well as the need for housewives to gain additional income. The training on the production of “Japan Instan” in Mendalo Indah Village aims to empower the community, especially housewives and unemployed women, by developing creative economic activities through innovative and marketable prod ucts. Ginger was chosen as the main ingredient because of its well-known health benefits, such as relieving headaches, preventing colds, improving digestion and increasing appetite (stimulant). Ginger is also a commonly found local plant. The training covered the processing of ingredients, packaging and marketing strategies. Additionally, pandan leaves were utilized as an innovation to enhance the flavor and aroma, resulting in a healthy instant beverage product